The green transition: a fundamental reconsideration of land rights and usage - Boccaletti, Giulio (Henry Stewart Talks, 2022)
Green transition, Land value, Bio-diversity, Role of the landscape, Property rights, National landscape, Geo-spatial information, Geographic footprint, Transparency, Regenerative agriculture